Shining Light on Poly(ethylene glycol) From Polymer Modification to 3D Laser Printing of Water Erasable Microstructures - Houck, Hannes A (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 The Authors. Published by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.